Existence of Solutions of Second-Order Partial Neutral Functional Differential Equations with Infinite Delay - Henriquez-Miranda, H (2011)
In this paper we establish the existence of mild solutions for a class of abstract second-order partial neutral functional differential equations with infinite delay in a Banach space. Copyright © 2011 Rocky Mountain Mathematics Consortium.